PPO.17 Is congenital heart disease on the increase in the UK? A register-based study. (9th June 2014) - Best, KE; Draper, E; Kurinczuk, J; Stoianova, S; Tucker, D; Wellesley, D; Rankin, J
Abstract : Aim: The aim of this study was to describe trends in the prevalence of congenital heart disease (CHD) according to severity and adjusted for maternal age. Methods: All CHD cases notified to six British Isles Network of Congenital Anomaly Registers between 1991–2010 formed this population-based study. Prevalence and 95% confidence intervals (CIs) were calculated as the number of cases (occurring in live births, fetal deaths or terminations for fetal anomaly) per 10, 000 live and stillbirths. Relative risks (RRs) of CHD over time, adjusted for maternal age were estimated using multilevel Poisson models. Results: There were 19, 353 singleton cases of CHD among 3, 040, 952 total births. Excluding, 2, 848 (14.7%) cases with a chromosomal anomaly, 683 (3.6%) with a genetic syndrome and 2, 639 (15.8%) with extra-cardiac anomalies, there were 13, 183 isolated cases. Of these, 7, 150 (54.2%, Prevalence = 23.51; 95% CI: 22.97–24.06 per 10, 000 total births) were classed as mild, 3, 204 (24.3%, Prevalence = 10.54; 95% CI: 10.18–10.91) as moderate and 1, 143 (8.7%, Prevalence = 3.76 95%; CI: 3.54–3.98) as severe CHD. There were no significant trends in prevalence over time in mild (RR = 1.04; 95% CI:. 99–1.10; p = 0.096), moderate (RR = 0.99; 95% CI: 0.99–1.00; p = 0.168) or severe CHD (RR = 1.01; 95% CI: 1.00–1.02; p = 0.074), even after adjustment for maternal age. The risk of a pregnancy associated with a mild CHD was significantly greater in women aged 35 and over compared to aged 20–29 (RR = 1.16; 95% CI:1.04–1.29; p = 0.009). Conclusion: There were no significant differences in trends in the prevalence by CHD severity, before or after adjustment for maternal age.